Analisis Yuridis Tanggungjawab Kepolisian Daerah Sumatera Selatan Dalam Menangani Pelaku Tindak Pidana Yang Melarikan Diri - Tri Setia Andrian; Aditya, Fariz Nayoan (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
The police’s responsibility to handle fugitive suspects, including verifying their status on the Wanted Persons List, is a critical component of the law enforcement process. However, there is currently no clear legal basis within Indonesia’s criminal justice system specifically the Criminal Procedure Code (KUHAP) for establishing the Wanted Persons List. To examine this issue, this study employs an empirical approach. The findings indicate that the regulations governing the Wanted Persons List are inconsistent with the law, which may violate legal certainty and the principle of non-discrimination. Additionally, there is a lack of harmonization among regulations and weaknesses in technical implementation. Furthermore, the operation of the Wanted Persons List faces challenges such as a lack of regulations, poor coordination among agencies, and technical issues, which hinder law enforcement. Therefore, to improve efficiency and legal stability in managing the Wanted Persons List, a comprehensive legal overhaul regarding the system is necessary, along with strengthened cooperation among law enforcement agencies, including international cooperation.